Implementación de un Sistema de Información Geográfica para la categorización de los posibles pasivos ambientales en Colombia (2022)
The implementation of a geographic information system that receives data on environmental impacts, processes and delivers them classified as environmental liability or as a resolved event, would allow the institutions involved in their management to have a consolidated base and instruments for capture, storage and consultation with interoperable data, which, following a structure of steps allows the classification of events as active, closed, declared liability or finally as orphan liabilities to proceed accordingly with the necessary legal and budgetary instruments.